Household wealth is associated with child stunting but not wasting: Evidence from the 2024 Nigeria Demographic and Health Survey - John Adeleke (PLOS One, 2026)
Child undernutrition remains a significant population health challenge in Nigeria and sub-Saharan Africa. Existing research has established an association between socioeconomic factors and child undernutrition, but less attention has been paid to whether the socioeconomic gradient is similar across indicators that capture different underlying processes. Drawing on fundamental cause theory, this study examines the association between household wealth and child stunting and wasting in Nigeria, and the extent to which that association is attenuated by other socioeconomic and geographic factors. Using the 2024 Nigeria Demographic and Health Survey (n = 9,410 children for stunting; n = 9,464 for wasting), Survey-weighted logistic regression models were fitted, using stepwise model building and joint tests of interaction. Household wealth was associated with stunting in a graded pattern but showed no association with wasting. The findings suggest that chronic and acute undernutrition may not share the same social determinants and may call for different interventions.